Wear-resistant composite polishing powder and preparation method thereof

Through the combination of the modified hexagonal boron -nitride@氧 铈 composite core objects and wear -resistant and efficient protective layers, the problem of lack of abrasion resistance and dispersability of the polished oxide polishing powder, and achieve higher abrasion resistance and Polishing effect.

CN119371896AActive Publication Date: 2025-01-28ZHENJIANG RISP NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411468353.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-28
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The cerium-based oxide polishing powder has low wear resistance and is prone to agglomeration during use, poor dispersion, which affects service life and polishing effect.

Method used

Adopt modified hexagonal boron -nitride@oxidation and composite core objects and wear -resistant and efficient protective layers, and use sodium hydroxide assisted physical ball grinding and water heating method to perform hydroxygenic modification to improve the dispersability and wetting of boron -nitride of hexagonal nitrogen , And to form a protective layer on the surface of the core object with copper oxide, enhance wear resistance.

Benefits of technology

A significant improvement of the abrasion resistance and decentralization of polishing powder, extending the service life, and improving the polishing efficiency and effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371896A_ABST
    Figure CN119371896A_ABST
Patent Text Reader

Abstract

The invention discloses wear-resistant composite polishing powder and a preparation method thereof, and relates to the technical field of polishing powder preparation. The wear-resistant composite polishing powder is composed of a modified hexagonal boron nitride and cerium oxide composite core and a wear-resistant synergistic protection layer, the modified hexagonal boron nitride and cerium oxide composite core material is prepared from a modified hexagonal boron nitride carrier, cerium oxide, polyvinylpyrrolidone and samarium oxide; a modified hexagonal boron nitride carrier is completely coated with main-phase cerium oxide, the main-phase cerium oxide and samarium oxide on the modified hexagonal boron nitride carrier form doping, a modified hexagonal boron nitride and cerium oxide composite core material is obtained, then copper oxide is loaded on the surface of the core material, a wear-resistant synergistic protection layer is formed, the wear resistance of the composite polishing powder is effectively enhanced, and the service life of the composite polishing powder is prolonged. The composite polishing powder provided by the invention reduces the loss in the use process, is beneficial to prolonging the service life, also improves the dispersibility of the composite polishing powder, further enhances the durability, and realizes an excellent polishing effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polishing powder preparation, and specifically refers to a wear-resistant composite polishing powder and a preparation method thereof. Background Art

[0002] Chemical mechanical polishing technology is a method that can achieve local and global flatness of silicon wafers and is widely used in the flattening treatment of Si wafer surfaces. Currently, the most commonly used grinding and polishing materials in the world are cerium-based oxides with cerium oxide or lanthanum oxide as the main components. These cerium-based oxide polishing powders are mostly used with water as a dispersant and are mixed into a slurry before use; cerium-based oxide polishing powders have unique physical and chemical properties and excellent polishing performance as well as low pollution to Si wafers, and are widely used in many fields such as mobile phone covers, optical glass, liquid crystal displays, crystal jewelry, integrated circuits, and precision optical components; however, with the development of science and technology and people's more stringent requirements on the quality of silicon wafers, simple cerium oxide polishing powders can no longer meet the process requirements, so there is an urgent need to improve cerium oxide and cerium-based oxide polishing powders to meet the increasingly high production standards.

[0003] The existing technology currently has the following problems:

[0004] The wear resistance of cerium-based oxide polishing powder is average, and it is easy to agglomerate during use and has poor dispersion, which has an adverse effect on the service life and polishing effect of the cerium-based oxide polishing powder. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes a wear-resistant composite polishing powder, comprising the following components in parts by weight: 80-100 parts of modified hexagonal boron nitride@cerium oxide composite core material and 10-25 parts of wear-resistant synergistic protective layer.

[0006] The modified hexagonal boron nitride@cerium oxide composite core material comprises the following components in parts by weight: 10-20 parts of modified hexagonal boron nitride carrier, 30-50 parts of cerium oxide, 10-20 parts of polyvinyl pyrrolidone, and 8-12 parts of samarium oxide.

[0007] The modified hexagonal boron nitride carrier is subjected to sodium hydroxide-assisted physical ball milling to peel the hexagonal boron nitride into nanosheets and perform preliminary hydroxylation modification at the same time, and then further perform hydroxylation modification by a hydrothermal method.

[0008] The wear-resistant synergistic protective layer is a shell material formed by using copper nitrate as a surface modification component and the obtained copper oxide is loaded on a core material.

[0009] The preparation method of the modified hexagonal boron nitride carrier specifically comprises the following steps:

[0010] (1) Add 20mL of 5mol / L sodium hydroxide solution and zirconium oxide grinding balls and hexagonal boron nitride powder in a mass ratio of 20:1 into a ball mill, control the rotation speed to 300-400rpm, grind for 12-24h, sieve, centrifuge the obtained hexagonal boron nitride slurry, centrifuge at a speed of 1000-2000rpm, centrifuge for 5-10min, take the upper suspension, centrifuge again, centrifuge at a speed of 9000-10000rpm, centrifuge for 5-10min, freeze-dry the precipitate, and use sodium hydroxide-assisted physical ball milling to peel the hexagonal boron nitride into nanosheets and perform preliminary hydroxylation modification, thereby reducing the adverse phenomenon caused by the agglomeration of the hexagonal boron nitride and improving the wettability, thereby obtaining hexagonal boron nitride nanosheet powder;

[0011] (2) 1.0-2.0 g of the hexagonal boron nitride nanosheet powder described in step (1) is added to 150 mL of a 5 mol / L sodium hydroxide solution, mixed evenly with a magnetic stirrer, and then subjected to ultrasonic dispersion treatment. The mixed solution is poured into a three-necked flask and refluxed in an oil bath at 100-120° C. for 24 h. The resulting solution is cooled and filtered, and washed with a 1 mol / L hydrochloric acid solution and deionized water respectively until the solution is neutral to fully remove the residual sodium hydroxide, and then freeze-dried. The hexagonal boron nitride nanosheet powder is further hydroxylated by a sodium hydroxide hydrothermal method to improve its wettability and dispersibility in aqueous solution, thereby obtaining a modified hexagonal boron nitride carrier;

[0012] Preferably, in step (2), during the ultrasonic dispersion process, the ultrasonic power is 600-800 W and the ultrasonic time is 20-30 min. The ultrasonic dispersion treatment is conducive to better contact modification of the hexagonal boron nitride nanosheet powder with the sodium hydroxide solution.

[0013] The present invention also provides a method for preparing the wear-resistant composite polishing powder, which specifically comprises the following steps:

[0014] S1. Add 1.0-2.0 g of modified hexagonal boron nitride carrier to 100 mL of deionized water, add 0.8-1.2 g of samarium nitrate hexahydrate, stir to mix evenly, and set aside. Weigh 3.0-5.0 g of cerium nitrate hexahydrate and 1.0-2.0 g of polyvinyl pyrrolidone powder and dissolve them in a mixed solution of 150 mL of ethylene glycol and 10 mL of deionized water, stir for 1 hour, then add the mixed solution of modified hexagonal boron nitride carrier and samarium nitrate hexahydrate, stir evenly, transfer the solution to a 400 mL polytetrafluoroethylene-lined stainless steel reactor, put it into a microwave hydrothermal reaction tank, and after the reaction is completed, naturally cool to room temperature, centrifuge the product, wash it with deionized water and anhydrous ethanol solution for 3-5 times, and then put it into a drying oven. The cerium oxide is prepared by mixing with samarium oxide in a mixing oven, drying at 50-60°C for 12 hours, and calcining in an air atmosphere at 400-500°C in a muffle furnace for 2-3 hours. Through hydrothermal reaction and calcination, a small amount of samarium oxide is loaded on the modified hexagonal boron nitride carrier as the core component. The two work synergistically to improve the dispersibility and suspension of the cerium oxide polishing powder in the form of doping and carrier, and improve the polishing uniformity and polishing efficiency. The main phase material cerium oxide is then completely coated with samarium oxide and the modified hexagonal boron nitride carrier to form a composite structure, so that the cerium oxide obtains a favorable internal support body, effectively enhancing the hardness and chemical stability of the polishing powder, thereby maintaining good wear resistance and polishing performance during the polishing process, and obtaining a modified hexagonal boron nitride@cerium oxide composite core material;

[0015] S2, dissolving the modified hexagonal boron nitride @ cerium oxide composite core material described in step S1 in 100-200 mL of deionized water, ultrasonically dispersing for 10-20 min, adding copper nitrate powder, stirring continuously for 1-2 h, heating to 90 ° C, stirring and evaporating the solution to dryness, placing the product in a muffle furnace, and calcining in an air atmosphere at 400-500 ° C for 2-3 h. The obtained copper oxide is loaded on the surface of the modified hexagonal boron nitride @ cerium oxide composite core material to form a wear-resistant and synergistic protective layer, further reducing the loss and breakage of cerium oxide during polishing, and improving the wear resistance. This sandwich-like structure also reduces the agglomeration of cerium oxide polishing powder. In addition, it also significantly increases the concentration of oxygen vacancies in the abrasive, promotes the combination of Ce-O-Si bonds, and enhances the reaction activity, thereby improving the polishing efficiency and polishing effect, and obtaining a wear-resistant composite polishing powder;

[0016] Preferably, in step S1, during the microwave hydrothermal reaction, the temperature is controlled to be kept at 70-80° C. for 0.5-1 h, and then kept at 150-160° C. for 6-7 h. Under the microwave hydrothermal conditions, cerium oxide continuously grows on the modified hexagonal boron nitride carrier, so that the modified hexagonal boron nitride carrier is coated inside the cerium oxide;

[0017] Preferably, in step S2, the amount of copper nitrate added is 0.2-0.5 g, and the interaction between copper ions and cerium ions forms a redox pair, so that part of the tetravalent cerium ions are reduced to trivalent cerium ions, thereby improving the polishing performance of cerium oxide.

[0018] The beneficial effects achieved by the present invention are as follows:

[0019] The present invention obtains a modified hexagonal boron nitride@cerium oxide composite core by completely coating a main phase cerium oxide with a modified hexagonal boron nitride carrier and doping it with samarium oxide on the modified hexagonal boron nitride carrier. Then, copper oxide is loaded on the surface of the core to form a wear-resistant and synergistic protective layer, which effectively enhances the wear resistance of the composite polishing powder, reduces the loss during use, is beneficial to prolonging the service life, improves the dispersibility of the composite polishing powder, further enhances the durability, and achieves an excellent polishing effect. In the modified hexagonal boron nitride@cerium oxide composite core, cerium oxide grows on the modified hexagonal boron nitride carrier, completely coats the modified hexagonal boron nitride carrier, and is doped with samarium oxide loaded on the modified hexagonal boron nitride carrier. The dispersibility of cerium oxide is improved by doping and carrier, the agglomeration phenomenon in water is reduced, the uniformity and polishing efficiency of the modified hexagonal boron nitride are improved, and the The addition of boron carrier and samarium oxide makes the cerium oxide polishing powder more compact, reduces defects, improves the hardness of the cerium oxide polishing powder, and makes it more wear-resistant; the wear-resistant and synergistic protective layer is obtained by calcining copper oxide loaded on the surface of the modified hexagonal boron nitride@cerium oxide composite core material, forming a sandwich-like inclusion structure, further reducing the loss and breakage of cerium oxide during the polishing process, and improving the wear resistance. At the same time, it also promotes the reduction of part of the tetravalent cerium ions to trivalent cerium ions, increases the concentration of oxygen vacancies in the abrasive, and promotes the bonding of Ce-O-Si bonds, thereby improving the polishing efficiency and polishing effect of the cerium oxide polishing powder; the present invention uses a modified hexagonal boron nitride@cerium oxide composite core material and a wear-resistant and synergistic protective layer to prepare a wear-resistant composite polishing powder, which has excellent dispersibility and wear resistance, is conducive to achieving a better polishing effect, improves the polishing efficiency, and extends the service life of the polishing powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a transmission electron microscope image of the modified hexagonal boron nitride carrier prepared in Example 1 of the present invention;

[0021] Figure 2 This is a scanning electron microscope image of the wear-resistant composite polishing powder prepared in Example 1 of the present invention;

[0022] Figure 3 The results of the particle size reduction rate of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0023] Figure 4The polishing performance results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0026] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0027] The sources of the reagents used in the examples are as follows:

[0028] Hexagonal boron nitride CAS No: 10043-11-5, brand Innochem, product number A67186;

[0029] Hydrochloric acid CAS No: 7647-01-0, brand Innochem, product number A04558;

[0030] Samarium nitrate hexahydrate CAS No: 13759-83-6, brand Innochem, product number A28163;

[0031] Cerium nitrate hexahydrate CAS No: 10294-41-4, brand Innochem, product number A22708;

[0032] Polyvinylpyrrolidone CAS No: 9003-39-8, brand Innochem, product number A38579;

[0033] Ethylene glycol CAS No: 107-21-1, brand Innochem, product number A82640;

[0034] Copper nitrate CAS No: 3251-23-8, brand Macklin, product number C860751-100g;

[0035] Sodium hydroxide CAS No: 1310-73-2, brand Innochem, product number A36865;

[0036] Anhydrous ethanol CAS No: 64-17-5, brand Innochem, product number G00004.

[0037] Example 1

[0038] This embodiment proposes a wear-resistant composite polishing powder, comprising the following components in parts by weight: 100 parts of a modified hexagonal boron nitride@cerium oxide composite core material and 25 parts of a wear-resistant synergistic protective layer.

[0039] The modified hexagonal boron nitride@cerium oxide composite core material comprises the following components in parts by weight: 20 parts of modified hexagonal boron nitride carrier, 50 parts of cerium oxide, 20 parts of polyvinyl pyrrolidone, and 12 parts of samarium oxide.

[0040] The hexagonal boron nitride carrier is modified by physical ball milling assisted by sodium hydroxide, and the hexagonal boron nitride is exfoliated into nanosheets and initially hydroxylated, and then further hydroxylated by hydrothermal method.

[0041] The wear-resistant and synergistic protective layer is a shell material formed by using copper nitrate as a surface modification component and loading the obtained copper oxide on a core material.

[0042] The preparation method of the modified hexagonal boron nitride carrier specifically comprises the following steps:

[0043] (1) Add 20 mL of 5 mol / L sodium hydroxide solution and zirconium oxide grinding balls and hexagonal boron nitride powder in a mass ratio of 20:1 into a ball mill, control the speed to 400 rpm, grind for 24 h, sieve, centrifuge the obtained hexagonal boron nitride slurry at a centrifugal speed of 2000 rpm for 10 min, take the upper suspension, centrifuge again at a centrifugal speed of 10000 rpm for 10 min, freeze-dry the precipitate, and use sodium hydroxide-assisted physical ball milling to peel the hexagonal boron nitride into nanosheets and perform preliminary hydroxylation modification, thereby reducing the adverse phenomenon caused by the agglomeration of the hexagonal boron nitride and improving the wettability, thereby obtaining hexagonal boron nitride nanosheet powder;

[0044] (2) Add 2.0 g of the hexagonal boron nitride nanosheet powder described in step (1) to 150 mL of 5 mol / L sodium hydroxide solution, mix evenly with a magnetic stirrer, and then perform ultrasonic dispersion treatment. During the ultrasonic dispersion process, the ultrasonic power is 800 W and the ultrasonic time is 30 min. The ultrasonic dispersion treatment is conducive to better contact modification of the hexagonal boron nitride nanosheet powder with the sodium hydroxide solution. The mixed solution is poured into a three-necked flask and refluxed in an oil bath at 120° C. for 24 h. The resulting solution is cooled and filtered, and washed with 1 mol / L hydrochloric acid solution and deionized water respectively until the solution is neutral to fully remove the residual sodium hydroxide, and then freeze-dried. The hexagonal boron nitride nanosheet powder is further hydroxylated by a sodium hydroxide hydrothermal method to improve its wettability and dispersibility in aqueous solution to obtain a modified hexagonal boron nitride carrier.

[0045] This embodiment provides a method for preparing a wear-resistant composite polishing powder, which specifically comprises the following steps:

[0046] S1. Add 2.0 g of modified hexagonal boron nitride carrier to 100 mL of deionized water, add 1.2 g of samarium nitrate hexahydrate, stir to mix evenly, and set aside. Weigh 5.0 g of cerium nitrate hexahydrate and 2.0 g of polyvinyl pyrrolidone powder and dissolve them in a mixed solution of 150 mL of ethylene glycol and 10 mL of deionized water, stir for 1 hour, then add the mixed solution of modified hexagonal boron nitride carrier and samarium nitrate hexahydrate, stir evenly, transfer the solution to a 400 mL polytetrafluoroethylene-lined stainless steel reactor, and put it into a microwave hydrothermal reaction tank. During the microwave hydrothermal reaction, control the temperature at 80°C for 1 hour, and then keep it at 160°C for 7 hours. Under the microwave hydrothermal conditions, cerium oxide continues to grow on the modified hexagonal boron nitride carrier, so that the modified hexagonal boron nitride carrier is coated inside the cerium oxide. After the reaction is completed, cool naturally. to room temperature, centrifugally separate the product, wash it with deionized water and anhydrous ethanol solution for 5 times in sequence, then put it into an oven, dry it at 60°C for 12h, and calcine it in an air atmosphere at 500°C in a muffle furnace for 3h. Through hydrothermal reaction and calcination treatment, a small amount of samarium oxide is loaded on the modified hexagonal boron nitride carrier as the core component. The two work synergistically to improve the dispersibility and suspension of cerium oxide polishing powder in the form of doping and carrier, and improve the polishing uniformity and polishing efficiency. The main phase material cerium oxide is then completely coated with samarium oxide and the modified hexagonal boron nitride carrier to form a composite structure, so that cerium oxide obtains a favorable internal support, effectively enhancing the hardness and chemical stability of the polishing powder, thereby maintaining good wear resistance and polishing performance during the polishing process, and obtaining a modified hexagonal boron nitride@cerium oxide composite core material;

[0047] S2. Dissolve the modified hexagonal boron nitride @ cerium oxide composite core material described in step S1 in 200 mL of deionized water, ultrasonically disperse for 20 minutes, add copper nitrate powder, the amount of copper nitrate added is 0.5 g, the interaction between copper ions and cerium ions forms a redox pair, so that part of the tetravalent cerium ions are reduced to trivalent cerium ions, thereby improving the polishing performance of cerium oxide, continuously stir for 2 hours, heat to 90°C, stir and evaporate the solution to dryness, put the product into a muffle furnace, and calcine in an air atmosphere at 500°C for 3 hours. The obtained copper oxide is loaded on the surface of the modified hexagonal boron nitride @ cerium oxide composite core material to form a wear-resistant and synergistic protective layer, which further reduces the loss and breakage of cerium oxide during the polishing process and improves the wear resistance. This sandwich-like structure also reduces the agglomeration of cerium oxide polishing powder. In addition, it also significantly increases the concentration of oxygen vacancies in the abrasive, promotes the binding of Ce-O-Si bonds, and enhances the reaction activity, thereby improving the polishing efficiency and polishing effect, and obtaining a wear-resistant composite polishing powder.

[0048] In this example, the prepared modified hexagonal boron nitride carrier was subjected to transmission electron microscopy and the wear-resistant composite polishing powder was subjected to scanning electron microscopy to observe its microscopic morphology. Figure 1 This is a TEM image of the modified hexagonal boron nitride carrier prepared in Example 1, magnified 100,000 times. Figure 2 This is a SEM image of the wear-resistant composite polishing powder prepared in Example 1, magnified 10,000 times. Figure 1 The modified hexagonal boron nitride carrier prepared in this embodiment is in the form of a thin sheet, such as Figure 2 The wear-resistant composite polishing powder prepared in this embodiment is an inclusion compound.

[0049] Example 2

[0050] This embodiment proposes a wear-resistant composite polishing powder, which includes the following components in parts by weight: 80 parts of modified hexagonal boron nitride@cerium oxide composite core material and 10 parts of wear-resistant synergistic protective layer.

[0051] The modified hexagonal boron nitride@cerium oxide composite core material comprises the following components in parts by weight: 10 parts of modified hexagonal boron nitride carrier, 30 parts of cerium oxide, 10 parts of polyvinyl pyrrolidone, and 8 parts of samarium oxide.

[0052] The hexagonal boron nitride carrier is modified by physical ball milling assisted by sodium hydroxide, and the hexagonal boron nitride is exfoliated into nanosheets and initially hydroxylated, and then further hydroxylated by hydrothermal method.

[0053] The wear-resistant and synergistic protective layer is a shell material formed by using copper nitrate as a surface modification component and loading the obtained copper oxide on a core material.

[0054] The preparation method of the modified hexagonal boron nitride carrier specifically comprises the following steps:

[0055] (1) Add 20 mL of 5 mol / L sodium hydroxide solution and zirconium oxide grinding balls and hexagonal boron nitride powder in a mass ratio of 20:1 into a ball mill, control the speed to 300 rpm, grind for 12 h, sieve, centrifuge the obtained hexagonal boron nitride slurry at a centrifugal speed of 1000 rpm for 5 min, take the upper suspension, centrifuge again at a centrifugal speed of 9000 rpm for 5 min, freeze-dry the precipitate, and use sodium hydroxide-assisted physical ball milling to exfoliate the hexagonal boron nitride into nanosheets and perform preliminary hydroxylation modification, thereby reducing the adverse phenomenon caused by the agglomeration of the hexagonal boron nitride and improving the wettability, thereby obtaining hexagonal boron nitride nanosheet powder;

[0056] (2) 1.0 g of the hexagonal boron nitride nanosheet powder described in step (1) was added to 150 mL of a 5 mol / L sodium hydroxide solution, mixed evenly with a magnetic stirrer, and then subjected to ultrasonic dispersion treatment. During the ultrasonic dispersion process, the ultrasonic power was 600 W and the ultrasonic time was 20 min. The ultrasonic dispersion treatment was beneficial to better contact modification of the hexagonal boron nitride nanosheet powder with the sodium hydroxide solution. The mixed solution was poured into a three-necked flask and refluxed in an oil bath at 100° C. for 24 h. The resulting solution was cooled and filtered, and washed with 1 mol / L hydrochloric acid solution and deionized water respectively until the solution was neutral to fully remove the residual sodium hydroxide, and then freeze-dried. The hexagonal boron nitride nanosheet powder was further hydroxylated by a sodium hydroxide hydrothermal method to improve its wettability and dispersibility in aqueous solution to obtain a modified hexagonal boron nitride carrier.

[0057] This embodiment provides a method for preparing a wear-resistant composite polishing powder, which specifically comprises the following steps:

[0058] S1. Add 1.0 g of modified hexagonal boron nitride carrier to 100 mL of deionized water, add 0.8 g of samarium nitrate hexahydrate, stir to mix evenly, and set aside. Weigh 3.0 g of cerium nitrate hexahydrate and 1.0 g of polyvinyl pyrrolidone powder and dissolve them in a mixed solution of 150 mL of ethylene glycol and 10 mL of deionized water, stir for 1 hour, then add the mixed solution of modified hexagonal boron nitride carrier and samarium nitrate hexahydrate, stir evenly, transfer the solution to a 400 mL polytetrafluoroethylene-lined stainless steel reactor, and put it into a microwave hydrothermal reaction tank. During the microwave hydrothermal reaction, control the temperature at 70°C for 0.5 h, and then keep it at 150°C for 6 h. Under microwave hydrothermal conditions, cerium oxide continues to grow on the modified hexagonal boron nitride carrier, so that the modified hexagonal boron nitride carrier is coated inside the cerium oxide. After the reaction is completed, naturally cool After cooling to room temperature, the product was centrifuged, washed with deionized water and anhydrous ethanol solution for 3 times, then placed in an oven, dried at 50°C for 12 hours, and calcined in an air atmosphere at 400°C in a muffle furnace for 2 hours. Through hydrothermal reaction and calcination treatment, a small amount of samarium oxide was loaded on the modified hexagonal boron nitride carrier as the core component. The two acted synergistically to improve the dispersibility and suspension of cerium oxide polishing powder in the form of doping and carrier, and improved the polishing uniformity and polishing efficiency. The main phase material cerium oxide was then completely coated with samarium oxide and the modified hexagonal boron nitride carrier to form a composite structure, so that cerium oxide obtained a favorable internal support, effectively enhancing the hardness and chemical stability of the polishing powder, thereby maintaining good wear resistance and polishing performance during the polishing process, and obtaining a modified hexagonal boron nitride @ cerium oxide composite core material;

[0059] S2. Dissolve the modified hexagonal boron nitride @ cerium oxide composite core material described in step S1 in 100 mL of deionized water, ultrasonically disperse for 10 minutes, add copper nitrate powder, the amount of copper nitrate added is 0.2 g, the interaction between copper ions and cerium ions forms a redox pair, so that part of the tetravalent cerium ions are reduced to trivalent cerium ions, thereby improving the polishing performance of cerium oxide, continuously stir for 1 hour, heat to 90°C, stir and evaporate the solution to dryness, put the product into a muffle furnace, and calcine in an air atmosphere at 400°C for 2 hours. The obtained copper oxide is loaded on the surface of the modified hexagonal boron nitride @ cerium oxide composite core material to form a wear-resistant and synergistic protective layer, which further reduces the loss and breakage of cerium oxide during the polishing process and improves the wear resistance. This sandwich-like structure also reduces the agglomeration of cerium oxide polishing powder. In addition, it also significantly increases the concentration of oxygen vacancies in the abrasive, promotes the binding of Ce-O-Si bonds, and enhances the reaction activity, thereby improving the polishing efficiency and polishing effect, and obtaining a wear-resistant composite polishing powder.

[0060] Example 3

[0061] This embodiment proposes a wear-resistant composite polishing powder, which includes the following components in parts by weight: 90 parts of modified hexagonal boron nitride@cerium oxide composite core material and 17.5 parts of wear-resistant synergistic protective layer.

[0062] The modified hexagonal boron nitride@cerium oxide composite core material comprises the following components in parts by weight: 15 parts of modified hexagonal boron nitride carrier, 40 parts of cerium oxide, 15 parts of polyvinyl pyrrolidone, and 10 parts of samarium oxide.

[0063] The hexagonal boron nitride carrier is modified by physical ball milling assisted by sodium hydroxide, and the hexagonal boron nitride is exfoliated into nanosheets and initially hydroxylated, and then further hydroxylated by hydrothermal method.

[0064] The wear-resistant and synergistic protective layer is a shell material formed by using copper nitrate as a surface modification component and loading the obtained copper oxide on a core material.

[0065] The preparation method of the modified hexagonal boron nitride carrier specifically comprises the following steps:

[0066] (1) Add 20 mL of 5 mol / L sodium hydroxide solution and zirconium oxide grinding balls and hexagonal boron nitride powder in a mass ratio of 20:1 into a ball mill, control the speed to 350 rpm, grind for 18 h, sieve, centrifuge the obtained hexagonal boron nitride slurry at a centrifugal speed of 1500 rpm for 7.5 min, take the upper suspension, centrifuge again at a centrifugal speed of 9500 rpm for 7.5 min, freeze-dry the precipitate, and use sodium hydroxide-assisted physical ball milling to exfoliate the hexagonal boron nitride into nanosheets and perform preliminary hydroxylation modification, thereby reducing the adverse phenomenon caused by the agglomeration of the hexagonal boron nitride and improving the wettability, thereby obtaining hexagonal boron nitride nanosheet powder;

[0067] (2) 1.5 g of the hexagonal boron nitride nanosheet powder described in step (1) was added to 150 mL of a 5 mol / L sodium hydroxide solution, mixed evenly with a magnetic stirrer, and then subjected to ultrasonic dispersion treatment. During the ultrasonic dispersion process, the ultrasonic power was 700 W and the ultrasonic time was 25 min. The ultrasonic dispersion treatment was beneficial to better contact modification of the hexagonal boron nitride nanosheet powder with the sodium hydroxide solution. The mixed solution was poured into a three-necked flask and refluxed in an oil bath at 110° C. for 24 h. The resulting solution was cooled and filtered, and washed with 1 mol / L hydrochloric acid solution and deionized water respectively until the solution was neutral to fully remove the residual sodium hydroxide, and then freeze-dried. The hexagonal boron nitride nanosheet powder was further hydroxylated by a sodium hydroxide hydrothermal method to improve its wettability and dispersibility in aqueous solution to obtain a modified hexagonal boron nitride carrier.

[0068] This embodiment provides a method for preparing a wear-resistant composite polishing powder, which specifically comprises the following steps:

[0069] S1. Add 1.5 g of modified hexagonal boron nitride carrier to 100 mL of deionized water, add 1.0 g of samarium nitrate hexahydrate, stir to mix evenly, and set aside. Weigh 4.0 g of cerium nitrate hexahydrate and 1.5 g of polyvinyl pyrrolidone powder and dissolve them in a mixed solution of 150 mL of ethylene glycol and 10 mL of deionized water, stir for 1 hour, then add the mixed solution of modified hexagonal boron nitride carrier and samarium nitrate hexahydrate, stir evenly, transfer the solution to a 400 mL polytetrafluoroethylene-lined stainless steel reactor, and put it into a microwave hydrothermal reaction tank. During the microwave hydrothermal reaction, control the temperature at 75 ° C for 0.75 h, and then keep it at 155 ° C for 6.5 h. Under microwave hydrothermal conditions, cerium oxide continues to grow on the modified hexagonal boron nitride carrier, so that the modified hexagonal boron nitride carrier is coated inside the cerium oxide. After the reaction is completed, naturally After cooling to room temperature, the product was centrifuged, washed with deionized water and anhydrous ethanol solution for 4 times, then placed in an oven, dried at 55°C for 12 hours, and calcined in an air atmosphere at 450°C in a muffle furnace for 2.5 hours. Through hydrothermal reaction and calcination treatment, a small amount of samarium oxide was loaded on the modified hexagonal boron nitride carrier as the core component. The two acted synergistically to improve the dispersibility and suspension of cerium oxide polishing powder in the form of doping and carrier, and improved the polishing uniformity and polishing efficiency. The main phase material cerium oxide was then completely coated with samarium oxide and the modified hexagonal boron nitride carrier to form a composite structure, so that cerium oxide obtained a favorable internal support, effectively enhancing the hardness and chemical stability of the polishing powder, thereby maintaining good wear resistance and polishing performance during the polishing process, and obtaining a modified hexagonal boron nitride @ cerium oxide composite core material;

[0070] S2. Dissolve the modified hexagonal boron nitride @ cerium oxide composite core material described in step S1 in 150 mL of deionized water, ultrasonically disperse for 15 minutes, add copper nitrate powder, the amount of copper nitrate added is 0.35 g, the interaction between copper ions and cerium ions forms a redox pair, so that part of the tetravalent cerium ions are reduced to trivalent cerium ions, thereby improving the polishing performance of cerium oxide, continuously stir for 1.5 hours, heat to 90°C, stir and evaporate the solution to dryness, put the product into a muffle furnace, and calcine in an air atmosphere at 450°C for 2.5 hours. The obtained copper oxide is loaded on the surface of the modified hexagonal boron nitride @ cerium oxide composite core material to form a wear-resistant and synergistic protective layer, which further reduces the loss and breakage of cerium oxide during the polishing process and improves the wear resistance. This sandwich-like structure also reduces the agglomeration of cerium oxide polishing powder. In addition, it also significantly increases the concentration of oxygen vacancies in the abrasive, promotes the binding of Ce-O-Si bonds, and enhances the reaction activity, thereby improving the polishing efficiency and polishing effect, and obtaining a wear-resistant composite polishing powder.

[0071] Example 4

[0072] This embodiment proposes a wear-resistant composite polishing powder, which includes the following components in parts by weight: 100 parts of modified hexagonal boron nitride@cerium oxide composite core material and 10 parts of wear-resistant synergistic protective layer.

[0073] The modified hexagonal boron nitride@cerium oxide composite core material comprises the following components in parts by weight: 20 parts of modified hexagonal boron nitride carrier, 50 parts of cerium oxide, 20 parts of polyvinyl pyrrolidone, and 8 parts of samarium oxide.

[0074] The hexagonal boron nitride carrier is modified by physical ball milling assisted by sodium hydroxide, and the hexagonal boron nitride is exfoliated into nanosheets and initially hydroxylated, and then further hydroxylated by hydrothermal method.

[0075] The wear-resistant and synergistic protective layer is a shell material formed by using copper nitrate as a surface modification component and loading the obtained copper oxide on a core material.

[0076] The preparation method of the modified hexagonal boron nitride carrier specifically comprises the following steps:

[0077] (1) Add 20 mL of 5 mol / L sodium hydroxide solution and zirconium oxide grinding balls and hexagonal boron nitride powder in a mass ratio of 20:1 into a ball mill, control the speed to 400 rpm, grind for 12 h, sieve, centrifuge the obtained hexagonal boron nitride slurry at a centrifugal speed of 2000 rpm for 5 min, take the upper suspension, centrifuge again at a centrifugal speed of 10000 rpm for 5 min, freeze-dry the precipitate, and use sodium hydroxide-assisted physical ball milling to peel the hexagonal boron nitride into nanosheets and perform preliminary hydroxylation modification, thereby reducing the adverse phenomenon caused by the agglomeration of the hexagonal boron nitride and improving the wettability, thereby obtaining hexagonal boron nitride nanosheet powder;

[0078] (2) Add 2.0 g of the hexagonal boron nitride nanosheet powder described in step (1) to 150 mL of 5 mol / L sodium hydroxide solution, mix evenly with a magnetic stirrer, and then perform ultrasonic dispersion treatment. During the ultrasonic dispersion process, the ultrasonic power is 800 W and the ultrasonic time is 20 min. The ultrasonic dispersion treatment is conducive to better contact modification of the hexagonal boron nitride nanosheet powder with the sodium hydroxide solution. The mixed solution is poured into a three-necked flask and refluxed in an oil bath at 120° C. for 24 h. The resulting solution is cooled and filtered, and washed with 1 mol / L hydrochloric acid solution and deionized water respectively until the solution is neutral to fully remove the residual sodium hydroxide, and then freeze-dried. The hexagonal boron nitride nanosheet powder is further hydroxylated by a sodium hydroxide hydrothermal method to improve its wettability and dispersibility in aqueous solution to obtain a modified hexagonal boron nitride carrier.

[0079] This embodiment provides a method for preparing a wear-resistant composite polishing powder, which specifically comprises the following steps:

[0080] S1. Add 2.0 g of modified hexagonal boron nitride carrier to 100 mL of deionized water, add 0.8 g of samarium nitrate hexahydrate, stir to mix evenly, and set aside. Weigh 5.0 g of cerium nitrate hexahydrate and 2.0 g of polyvinyl pyrrolidone powder and dissolve them in a mixed solution of 150 mL of ethylene glycol and 10 mL of deionized water, stir for 1 hour, then add the mixed solution of modified hexagonal boron nitride carrier and samarium nitrate hexahydrate, stir evenly, transfer the solution to a 400 mL polytetrafluoroethylene-lined stainless steel reactor, and put it into a microwave hydrothermal reaction tank. During the microwave hydrothermal reaction, control the temperature at 80°C for 0.5 h, and then keep it at 160°C for 6 h. Under microwave hydrothermal conditions, cerium oxide continues to grow on the modified hexagonal boron nitride carrier, so that the modified hexagonal boron nitride carrier is coated inside the cerium oxide. After the reaction is completed, naturally cool After cooling to room temperature, the product was centrifuged, washed with deionized water and anhydrous ethanol solution for 5 times, then placed in an oven, dried at 60°C for 12 hours, and calcined in an air atmosphere at 500°C in a muffle furnace for 2 hours. Through hydrothermal reaction and calcination treatment, a small amount of samarium oxide was loaded on the modified hexagonal boron nitride carrier as the core component. The two acted synergistically to improve the dispersibility and suspension of cerium oxide polishing powder in the form of doping and carrier, and improve the polishing uniformity and polishing efficiency. The main phase material cerium oxide was then completely coated with samarium oxide and the modified hexagonal boron nitride carrier to form a composite structure, so that cerium oxide obtained a favorable internal support, effectively enhancing the hardness and chemical stability of the polishing powder, thereby maintaining good wear resistance and polishing performance during the polishing process, and obtaining a modified hexagonal boron nitride @ cerium oxide composite core material;

[0081] S2. Dissolve the modified hexagonal boron nitride @ cerium oxide composite core material described in step S1 in 200 mL of deionized water, ultrasonically disperse for 10 minutes, add copper nitrate powder, the amount of copper nitrate added is 0.2 g, the interaction between copper ions and cerium ions forms a redox pair, so that part of the tetravalent cerium ions are reduced to trivalent cerium ions, thereby improving the polishing performance of cerium oxide, continuously stir for 1 hour, heat to 90°C, stir and evaporate the solution to dryness, put the product into a muffle furnace, and calcine at 500°C in an air atmosphere for 2 hours. The obtained copper oxide is loaded on the surface of the modified hexagonal boron nitride @ cerium oxide composite core material to form a wear-resistant and synergistic protective layer, which further reduces the loss and breakage of cerium oxide during the polishing process and improves the wear resistance. This sandwich-like structure also reduces the agglomeration phenomenon of cerium oxide polishing powder. In addition, it also significantly increases the concentration of oxygen vacancies in the abrasive, promotes the binding of Ce-O-Si bonds, and enhances the reaction activity, thereby improving the polishing efficiency and polishing effect, and obtaining a wear-resistant composite polishing powder.

[0082] Comparative Example 1

[0083] This comparative example provides a wear-resistant composite polishing powder, which differs from Example 1 in that the wear-resistant composite polishing powder does not contain a modified hexagonal boron nitride carrier; the preparation method of the wear-resistant composite polishing powder in step S1 does not contain a modified hexagonal boron nitride carrier, and other contents are the same as Example 1.

[0084] Comparative Example 2

[0085] This comparative example provides a wear-resistant composite polishing powder, which differs from Example 1 in that the wear-resistant composite polishing powder does not contain samarium oxide; the preparation method of the modified hexagonal boron nitride carrier is the same as that of Example 1; the preparation method of the wear-resistant composite polishing powder does not contain samarium nitrate hexahydrate in step S1, and the other contents are the same as those of Example 1.

[0086] Comparative Example 3

[0087] This comparative example provides a wear-resistant composite polishing powder, which differs from Example 1 in that the wear-resistant composite polishing powder does not contain a wear-resistant synergistic protective layer; the preparation method of the modified hexagonal boron nitride carrier is the same as that of Example 1; and the preparation method of the wear-resistant composite polishing powder does not include step S2.

[0088] Experimental Example 1

[0089] Wear resistance test

[0090] Test samples: wear-resistant composite polishing powders prepared in Examples 1-4 and Comparative Examples 1-3.

[0091] Test method: The test samples were dispersed in deionized water to prepare a suspension with a mass fraction of 1%. The pH value of the suspension was adjusted to 9.0 with 0.1 mol / L NaOH solution. The polishing liquid was ultrasonically dispersed for 5 minutes before use. The Shenyang Kejing UNIPOL-1200S automatic pressure grinding and polishing machine was used to polish a 2cm×2cm thermally oxidized silicon wafer. The polishing parameters were set as follows: upper plate speed of 80r / min, lower plate speed of 120r / min, pressure of 1kg, polishing time of 3min, polishing liquid flow rate of 100mL / min, and the central particle size (um) before and after polishing was counted. The particle size reduction rate (%) was calculated according to the following formula as a reference for the wear resistance of the polishing powder. The larger the reduction rate, the more obvious the particle size change and the poorer the wear resistance:

[0092] Particle size reduction rate (%) = (particle size before polishing - particle size after polishing) / particle size before polishing × 100%

[0093] Figure 3It is a result graph of the particle size reduction rate of Examples 1-4 and Comparative Examples 1-3; as shown in the figure, the particle size reduction rate of Examples 1-4 is 5-9%, all <10%, indicating that the wear resistance is strong; the particle size reduction rate of Comparative Examples 1-3 is 14-20%, all >10%, indicating that the wear resistance is weak; the wear-resistant composite polishing powder of Comparative Example 1 does not contain a modified hexagonal boron nitride carrier, cerium oxide cannot grow on the carrier to form a coating, lacks the support of the internal carrier, is not conducive to improving the hardness, resulting in weak wear resistance; the wear-resistant composite polishing powder of Comparative Example 2 does not contain samarium oxide, lacks the doping addition of samarium oxide, is not conducive to improving the density and defects of the cerium oxide polishing powder, resulting in weak wear resistance; the wear-resistant composite polishing powder of Comparative Example 3 does not contain a wear-resistant synergistic protective layer, and copper oxide cannot be loaded on the surface of the modified hexagonal boron nitride @ cerium oxide composite core, which is not conducive to reducing the breakage of cerium oxide during polishing, resulting in weak wear resistance.

[0094] Experimental Example 2

[0095] Polishing performance test

[0096] Test samples: wear-resistant composite polishing powders prepared in Examples 1-4 and Comparative Examples 1-3.

[0097] Test method: The test samples were dispersed in deionized water to prepare a suspension with a mass fraction of 1%. The pH value of the suspension was adjusted to 9.0 with a 0.1 mol / L NaOH solution. The polishing liquid was ultrasonically dispersed for 5 minutes before use. A 2cm×2cm thermally oxidized silicon wafer was polished using Shenyang Kejing UNIPOL-1200S automatic pressure grinding and polishing machine. The polishing parameters were set as follows: upper plate speed of 80r / min, lower plate speed of 120r / min, pressure of 1kg, polishing time of 3min, and polishing liquid flow rate of 100mL / min. The material removal rate (MRR) was defined as the change in film thickness per unit time. To ensure the authenticity of the data, the mass of the workpiece before and after polishing was weighed three times with a balance with an accuracy of one hundred thousandth and the average value was taken. The calculation formula is as follows;

[0098] Then, 150 thermally oxidized silicon wafers were polished using different test samples for testing. Those with scratches were classified as defective products, and the yield rate (%) was calculated.

[0099] MRR (nm / min) = m 差值 / (ρ×S×t)

[0100] Among them, m 差值 is the mass difference of the workpiece before and after polishing (g), ρ is the density of the silicon oxide film (valued at 2.2 g / cm 3 ), S is the Si wafer area (cm 2 ), t is the polishing time (min).

[0101] Figure 4 The polishing performance result diagram of Examples 1-4 and Comparative Examples 1-3 is as shown in the figure; as shown in the figure, the removal rate and yield rate of Examples 1-4 are 219.5-235.2nm / min and 96.6-99.3%, respectively, indicating that the polishing performance is good, and the polishing removal rate and yield rate are high; the removal rate and yield rate of Comparative Examples 1-3 are 174.5-201.3nm / min and 90.0-93.3%, respectively, indicating that the polishing performance is poor, and the polishing removal rate and yield rate are low; the wear-resistant composite polishing powder of Comparative Example 1 does not contain a modified hexagonal boron nitride carrier, and the dispersibility of cerium oxide cannot be improved in the form of a carrier, which increases the The agglomeration in water limits the polishing efficiency and polishing quality, resulting in poor polishing performance, low polishing removal rate and yield rate; the wear-resistant composite polishing powder of comparative example 2 does not contain samarium oxide, and cannot improve the dispersibility of cerium oxide by doping, nor can it exert the reduction-promoting effect of samarium oxide on cerium oxide, thereby failing to improve the polishing efficiency and surface flatness of the cerium oxide polishing powder, resulting in poor polishing performance, low polishing removal rate and yield rate; the wear-resistant composite polishing powder of comparative example 3 does not contain a wear-resistant synergistic protective layer, and cannot exert the active effect of copper oxide on cerium oxide, resulting in poor polishing performance, low polishing removal rate and yield rate.

[0102] The above experimental results show that the wear resistance and polishing performance of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3. Among them, Example 1 using a modified hexagonal boron nitride @ cerium oxide composite core and a wear-resistant synergistic protective layer has stronger wear resistance, higher polishing removal rate and higher yield rate. Cerium oxide grows on a modified hexagonal boron nitride carrier, completely covers the modified hexagonal boron nitride carrier, and is doped with samarium oxide loaded on the modified hexagonal boron nitride carrier. The dispersibility of cerium oxide is improved by doping and carrier, the agglomeration phenomenon in water is reduced, the uniformity and polishing efficiency of polishing are improved, and the modified hexagonal boron nitride carrier is improved. The addition of boron nitride carrier and samarium oxide makes the cerium oxide polishing powder more compact, reduces defects, improves the hardness of the cerium oxide polishing powder, and makes it more wear-resistant. Then the copper oxide obtained by calcination is loaded on the surface of the modified hexagonal boron nitride@cerium oxide composite core, forming a sandwich-like structure, which further reduces the loss and breakage of cerium oxide during the polishing process and improves the wear resistance. At the same time, it also promotes the reduction of some tetravalent cerium ions to trivalent cerium ions, increases the concentration of oxygen vacancies in the abrasive, and promotes the bonding of Ce-O-Si bonds, thereby improving the polishing efficiency and polishing effect of the cerium oxide polishing powder.

[0103] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0104] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A wear-resistant composite polishing powder, characterized in that: The wear-resistant composite polishing powder comprises the following components in parts by weight: 80-100 parts of a modified hexagonal boron nitride@cerium oxide composite core material and 10-25 parts of a wear-resistant synergistic protective layer; the modified hexagonal boron nitride@cerium oxide composite core material comprises the following components in parts by weight: 10-20 parts of a modified hexagonal boron nitride carrier, 30-50 parts of cerium oxide, 10-20 parts of polyvinyl pyrrolidone and 8-12 parts of samarium oxide; the modified hexagonal boron nitride carrier is subjected to physical ball milling assisted by sodium hydroxide to peel the hexagonal boron nitride into nanosheets and perform preliminary hydroxylation modification, and then further perform hydroxylation modification by a hydrothermal method; the wear-resistant synergistic protective layer is a shell material formed by loading copper oxide obtained by using copper nitrate as a surface modification component on a core material.

2. A method for preparing the wear-resistant composite polishing powder according to claim 1, characterized in that: The specific steps include: S1. Add 1.0-2.0 g of modified hexagonal boron nitride carrier to 100 mL of deionized water, add 0.8-1.2 g of samarium nitrate hexahydrate, stir to mix evenly, and set aside. Weigh 3.0-5.0 g of cerium nitrate hexahydrate and 1.0-2.0 g of polyvinyl pyrrolidone powder and dissolve them in a mixed solution of 150 mL of ethylene glycol and 10 mL of deionized water, stir for 1 hour, and then add the mixed solution of modified hexagonal boron nitride carrier and samarium nitrate hexahydrate. Stir evenly, transfer the solution to a 400mL polytetrafluoroethylene-lined stainless steel reactor, and place it in a microwave hydrothermal reaction tank. After the reaction is completed, cool it naturally to room temperature, centrifuge the product, wash it with deionized water and anhydrous ethanol solution for 3-5 times, then place it in an oven, dry it at 50-60°C for 12h, and calcine it in a muffle furnace at 400-500°C in an air atmosphere for 2-3h to obtain a modified hexagonal boron nitride@cerium oxide composite core; S2. Dissolve the modified hexagonal boron nitride @ cerium oxide composite core material described in step S1 in 100-200 mL of deionized water, ultrasonically disperse for 10-20 min, add copper nitrate powder, stir continuously for 1-2 h, heat to 90 ° C, stir and evaporate the solution to dryness, put the product into a muffle furnace, and calcine at 400-500 ° C in an air atmosphere for 2-3 h to form a wear-resistant and synergistic protective layer to obtain a wear-resistant composite polishing powder.

3. The method for preparing the wear-resistant composite polishing powder according to claim 2, characterized in that: In step S1, during the microwave hydrothermal reaction, the temperature is controlled to be kept at 70-80°C for 0.5-1h, and then kept at 150-160°C for 6-7h.

4. The method for preparing the wear-resistant composite polishing powder according to claim 3, characterized in that: In step S2, the amount of copper nitrate added is 0.2-0.5 g.

5. The method for preparing the wear-resistant composite polishing powder according to claim 4, characterized in that: The preparation method of the modified hexagonal boron nitride carrier specifically comprises the following steps: (1) Add 20 mL of 5 mol / L sodium hydroxide solution and zirconium oxide grinding balls and hexagonal boron nitride powder in a mass ratio of 20:1 into a ball mill, control the speed to 300-400 rpm, grind for 12-24 h, sieve, centrifuge the obtained hexagonal boron nitride slurry, centrifuge at a speed of 1000-2000 rpm, centrifuge for 5-10 min, take the upper suspension, centrifuge again, centrifuge at a speed of 9000-10000 rpm, centrifuge for 5-10 min, freeze-dry the precipitate to obtain hexagonal boron nitride nanosheet powder; (2) 1.0-2.0 g of the hexagonal boron nitride nanosheet powder described in step (1) is added to 150 mL of 5 mol / L sodium hydroxide solution, mixed evenly with a magnetic stirrer, and then subjected to ultrasonic dispersion treatment. The mixed solution is poured into a three-necked flask and refluxed in an oil bath at 100-120° C. for 24 h. The resulting solution is cooled and filtered, washed with 1 mol / L hydrochloric acid solution and deionized water respectively until the solution is neutral, and then freeze-dried to obtain a modified hexagonal boron nitride carrier.

6. The method for preparing the wear-resistant composite polishing powder according to claim 5, characterized in that: In step (2), during the ultrasonic dispersion process, the ultrasonic power is 600-800 W and the ultrasonic time is 20-30 min.

Citation Information

Patent Citations

  • Ultra-precise curved surface finishing method based on non-Newtonian fluid shear thickening effect

    CN102717325A

  • Ceramic composite cutter material and preparation method thereof

    CN107794465A

  • Chemical mechanical polishing of group iii-nitride surfaces

    US20120252213A1

  • Composite abrasive, method of preparing same, polishing slurry including same, and method of manufacturing semiconductor device

    US20230357616A1